A study of inhibitors of d-glycero-β-d-manno-heptose-1-phosphate adenylyltransferase from Burkholderia pseudomallei as a potential antibiotic target - Suwon Kim; Seri Jo; Mi-Sun Kim; Dong Hae Shin (Journal of Enzyme Inhibition and Medicinal Chemistry, 2021)
d-Glycero-β-d-manno-heptose-1-phosphate adenylyltransferase from Burkholderia pseudomallei (BpHldC) is the fourth enzyme in the ADP‐l‐glycero‐β‐d‐manno‐heptose biosynthesis pathway producing a lipopolysaccharide core. Therefore, BpHldC is an anti-melioidosis target. Three ChemBridge compounds purchased from ChemBridge Corporation (San Diego, CA) were found to have an effective inhibitory activity on BpHldC. Interestingly, ChemBridge 7929959 was the most effective compound due to the presence of the terminal benzyl group. The enzyme kinetic study revealed that most of them show mixed type inhibitory modes against ATP and βG1P. The induced-fit docking indicated that the medium affinity of ChemBridge 7929959 is originated from its benzyl group occupying the substrate-binding pocket of BpHldC. The inhibitory role of terminal aromatic groups was proven with ChemBridge 7570508. Combined with the previous study, ChemBridge 7929959 is found to work as a dual inhibitor against both HldC and HddC. Therefore, three ChemBridge compounds can be developed as a potent anti-melioidosis agent with a novel inhibitory concept.